2000
DOI: 10.1021/es9907156
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Desorption Mass Spectrometric Analysis of Organic Aerosol Formed from Reactions of 1-Tetradecene and O3 in the Presence of Alcohols and Carboxylic Acids

Abstract: The chemistry of secondary organic aerosol formation from reactions of 1-tetradecene and O3 in dry air in the presence of excess alcohols and carboxylic acids was investigated in an environmental chamber using a thermal desorption particle beam mass spectrometer. Temperature-programmed thermal desorption of collected aerosol shows that in each reaction two major aerosol products are formed. The more volatile compounds in each pair of products are α-alkoxytridecyl or α-acyloxytridecyl hydroperoxides, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
214
2
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(231 citation statements)
references
References 47 publications
11
214
2
4
Order By: Relevance
“…During the first several hours, the particle phase is dominated by first-to third-generation SVOCs, which are progressively converted to higher generation SVOCs in the gas phase and low volatility products in the particle phase. The contribution of particle-phase products to the total SOA budget is predicted to exceed 60% after ∼5 h. The dominance of low-volatility particle-phase products is consistent with previous studies, in which peroxyhemiacetals were found to be major products in SOA derived from oxidation of alkenes (1-tetradecene) (23,24), aromatic hydrocarbons (toluene) (25,26), and monoterpenes (α-and β-pinene) (27). Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…During the first several hours, the particle phase is dominated by first-to third-generation SVOCs, which are progressively converted to higher generation SVOCs in the gas phase and low volatility products in the particle phase. The contribution of particle-phase products to the total SOA budget is predicted to exceed 60% after ∼5 h. The dominance of low-volatility particle-phase products is consistent with previous studies, in which peroxyhemiacetals were found to be major products in SOA derived from oxidation of alkenes (1-tetradecene) (23,24), aromatic hydrocarbons (toluene) (25,26), and monoterpenes (α-and β-pinene) (27). Fig.…”
Section: Resultssupporting
confidence: 89%
“…1C). The particle-phase reactions are predicted to occur mainly at and near the surface, consistent with a product analysis study suggesting that PHA formation should occur mainly at the particle surface (24). Fig.…”
Section: Resultssupporting
confidence: 81%
“…Accurate mass measurements (Table 2) of selected OLI-D oligomers agree well with the expected elemental composition for these peroxyhemiacetals. Formation of peroxyhemiacetals has also been suggested in SOA from ozonolysis of 1-tetradecene, 69 a-pinene, 16,23 and ethylene, 44 and photooxidation of dodecane 70 and toluene. 71 Fig .…”
Section: Scavengermentioning
confidence: 95%
“…Several mechanisms for oligomer product formation in SOA arising from VOC oxidation have been proposed: i) self-and cross-reactions of the peroxy radicals (RO 2 ) (Zhang et al, 2016), ii) reaction of ozonolysis products in the condensed-phase, such as aldol condensation, esterification, hemiacetal and peroxyhemiacetal formation (Ziemann, 2003;Tolocka et al, 2004;Kristensen et al, 2014;Docherty et al, 2005;Muller et al, 2009;Yasmeen et al, 2010;Hall and Johnston, 2012;Witkowski and Gierczak, 2012;DePalma et al, 2013;Lim and Turpin, 2015), iii) dimer cluster formation from carboxylic acids 15 (Hoffmann et al, 1998;Tobias and Ziemann, 2000;Claeys et al, 2009;Camredon et al, 2010;DePalma et al, 2013), iv) reactions of Criegee intermediates (CIs) with VOCs oxidation products (Bonn et al, 2002;Lee and Kamens, 2005;Tolocka et al, 2006;Heaton et al, 2007;Witkowski and Gierczak, 2012;Kristensen et al, 2016;Wang et al, 2016), and vi) reactions of RO 2 radicals with Cis (Sadezky et al, 2008;Zhao et al, 2015). Among them, the reactions of CIs with protic substances (water, alcohols, acids and hydroperoxides) can form ROOH.…”
Section: (A)mentioning
confidence: 99%